2016
DOI: 10.1038/srep36465
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Ecotoxicity of Silver Nanoparticles Transferred from Escherichia coli to Caenorhabditis elegans

Abstract: Previous studies have indicated that engineered nanomaterials can be transferred through the food chain. However, their potential ecotoxicity to the environment is not fully understood. Here, we systematically evaluated the physiological behavior and toxicity of polyvinylpyrrolidone (PVP)-coated silver nanoparticles (AgNPs) using a food chain model from Escherichia coli (E. coli) to Caenorhabditis elegans (C. elegans). Our results demonstrated that AgNPs accumulated in E. coli could be transferred to the C. el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…The results revealed that some of the small Ag NPs remained in the digestive lumen, subcutaneous tissue, and gonad. This verified that the Ag NPs uptake at the intracellular level and only small particles or partial aggregation of silver nanoparticles were detected in the cells, whereas larger aggregation was not internalized in E. coli [29][30][31] .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The results revealed that some of the small Ag NPs remained in the digestive lumen, subcutaneous tissue, and gonad. This verified that the Ag NPs uptake at the intracellular level and only small particles or partial aggregation of silver nanoparticles were detected in the cells, whereas larger aggregation was not internalized in E. coli [29][30][31] .…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, the characteristic features of nanoparticles such as size, shape, density distribution have been demonstrated to affect the antibacterial activity of Ag NPs significantly, this could be attributed to a differential release of Ag + ions 10 . Previous researches in this field suggested that the effects of shapes and sizes prepared by wet chemical reduction methods or biosynthesis play a significant role in the antimicrobial nature of Ag NPs [11][12][13][14] . These methods have been devoted to controlling the size and shape of the Ag NPs, however, still, some obstacles such as the presence of colloidal stabilizers or impurities, the toxic solvents, and the sophisticated synthesis process to reduce or suppress the aggregation phenomenon in solution were detected [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…These are a combination of nano-specific effects and, in the case of biodegradable particles, also ion-related effects. Data extracted from Ma et al , Liu et al ,[93] Luo et al ,[94] Yu et al ,[67] Levy et al ,[95] Soenen et al ,[96, 97] Sabella et al ,[98] Ma et al [24] and Polak et al . [49]…”
Section: Figurementioning
confidence: 99%
“…Teratogenesis results in physical deformations (Hovland et al 2000) and in some cases behavioral aberrations (Weis 2014) that manifest later in life. A generational transfer of silver nanoparticles (NPs) from the parent was detected in the unexposed F1 generation of C. elegans (Luo et al 2016). There can also be a direct maternal transfer of metals to other generations (Kim et al 2013;Schultz et al 2016).…”
Section: Introductionmentioning
confidence: 99%